Do Feelings of Loneliness Mediate the Relationship between Sociocognitive Understanding and Depressive Symptoms During Late Childhood and Early Adolescence?. Issue 4 (4th July 2017) - Caputi, Marcella; Pantaleo, Giuseppe; Scaini, Simona
ABSTRACT: An interesting association between sociocognitive understanding and depression has been documented in clinical populations, with high levels of depression apparently related to theory-of-mind deficits. Yet no research has so far investigated this relationship among typically developing preadolescents. Therefore, the authors' main aim was to extend previous findings to the general population and to a younger age group. A secondary aim was to explore the role of feelings of loneliness referring to the previous link. A sociocognitive understanding task followed by self-report questionnaires on depressive symptoms and perceived loneliness were administered to a sample of 326 students attending primary and middle schools. Mediation analyses revealed that feelings of loneliness mediated the effect of sociocognitive understanding on depressive symptoms, but only among girls. In boys, depressive symptoms were directly linked to sociocognitive skills. In girls, on the contrary, the relationship between sociocognitive skills and depressive symptoms was significantly mediated by feelings of loneliness. Theoretical and practical implications of these findings are discussed.